Profesionalitas Pengacara dalam Pendampingan Klien Ditinjau dari Perspektif Pancasila - Octaviana Putri Maharani; Natal, Natal Kristiono (HK-Publishing, 2026)
Abstract This study aims to evaluate the professional responsibility of lawyers in protecting the rights of clients in every judicial process and to assess its application from the perspective of Pancasila values. The method used in this study is qualitative with a normative and empirical approach. The normative approach is carried out through an analysis of Law Number 18 of 2003 concerning Lawyers, professional codes of ethics, and legal principles related to the obligations of lawyers. while the empirical approach was conducted through in-depth interviews with lawyers, judges, and clients at the Pekalongan District Court, field observations, and document studies. The data obtained was analysed using qualitative descriptive techniques through the steps of reduction, presentation, and conclusion drawing using source triangulation to ensure accuracy. The research findings show that lawyer professionalism is a combination of legal ability, field experience, and moral integrity based on Pancasila values. Client rights protection is realised through assistance from the early stages of the legal process, legal education, preparation of realistic defence strategies, and compliance with the code of ethics, including the prohibition of guaranteeing victory. Challenges to professionalism arise in the form of pressure from clients, public perceptions of economic influence on decisions, and obstacles in the judicial system. This study emphasises that the professionalism of solicitors does not solely focus on the final outcome of a case, but also on a fair, transparent, and dignified process in accordance with the principles of Pancasila justice. Keywords: professional responsibility, protection of client rights, Pancasila values Abstrak Penelitian ini memiliki tujuan untuk mengevaluasi tanggung jawab profesional pengacara dalam menjaga hak klien disetiap proses peradilan dan untuk menilai penerapannya dari sudut pandang nilai-nilai pancasila. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan normatif dan empiris, pendekatan normatif dilakukan melalui analisis terhadap Undang-Undang Nomor 18 Tahun 2003 Tentang Pengacara, kode etik profesi serta prinsip-prinsip hukum yang berkaitan dengan kewajiban pengacara, sementara pendekatan empiris dilakukan melalui wawancara mendalam dengan pengacara, hakim, dan klien di Pengadilan Negeri Pekalongan, observasi lapangan danstudi dokumen. Data yang diperoleh dianalisis dengan menggunakan teknik deskriptif kualitatif melalui langkah-langkah reduksi, penyajian, dan penarikan kesimpulan dengan menggunakan trianggulasi sumber untuk memastikan akurasi. Temuan penelitian menunjukan bahwa profesionalisme pengacara merupakan kombinasi anatara kemampuan hukum, pengalaman lapangan, dan integritas moral yang berlandaskan nilai-nilai pancasila. Perlindungan hak klien diwujudkan melalui pendampingan sejak tahap awal proses hukum, edukasi hukum, penyiapan strategi pembelaan yang realistis, serta kepatuhan terhadap kode etik, termasuk larangan memberikan jaminan kemenangan. Tantangan terhadap profesionalitas muncul dalam bentuk tekanan dari klien, anggapan masyarakat mengenai pengaruh ekonomi terhadap keputusan, dan kendala dalam sistem peradilan. Penelitian ini menekankan bahwa profesionaluitas pengacara tidak semata-mata berfokus pada hasil akhir suatu perkara, tetapi juga pada proses yang adil, transparan, dan bermartabat sesuai dengan prinsip keadilan pancasila. Kata kunci: tanggung jawab profesional, perlindungan hak klien, nilai pancasila.